Pengaruh Budaya Organisasi terhadap Mutu Pendidikan di Sekolah - nurfajrina, sabila (Pedagogi: Jurnal Pendidikan Dasar, 2026)
School culture or school organizational culture currently plays a very important role in school development, especially regarding the quality of education. The purpose of this study was to determine the effect of organizational culture on the quality of education in schools. The research method used in this study is a Systematic Literature Review taken from Google Scholar for 2016-2022. The results obtained from this study indicate that there is a significant influence of organizational culture on the quality of education. The less leadership the school principal does and the lower the organizational culture, the lower the quality of education will be, and vice versa.